African American Population Percentage Negatively Mediates SES Association with Poor Mental Health - Rizzo, Toni (MD Conference Express, 2015)
Social inequities are strongly associated with health disparities. Research shows that chronic and traumatic social inequities can be epigenetic and complicate the health risks of inflammatory illnesses such as type 2 diabetes, cardiovascular disease, and depression. This article discusses the findings of this study which tested basic assumptions of the epigenetic biological link between social inequities and health disparities in African Americans living in the United States.